Evaluation of 1H‐NMR Spectroscopy‐Based Quantification Methods of the Supramolecular Aggregation of a Molecular Photosensitizer. (6th July 2022) - Pehlken, Christian; Pfeffer, Michael G.; Reich, Katharina; Rau, Sven
Abstract: The supramolecular dimerization of a ruthenium polypyridyl precursor of a well‐developed family of hydrogen‐evolving photocatalysts via π–π interactions of the polyheteroaromatic bridging ligand was quantified with concentration‐dependent 1 H‐NMR spectroscopy. The data sets were analyzed with different calculation and fit methods. A comparison between the results of direct calculation and linear and nonlinear approaches showed that the application of a global nonlinear fit procedure yields the best results. The presented methods are also applicable for dimerization processes in the solution of other molecular moieties. Abstract : π‐Expansive ligands are known to play a crucial role in many applications of their photoredox‐active transition metal complexes due to the intrinsic ability to form aggregates through stacking interactions. A reliable and consistent way of quantifying the self‐aggregation behavior of such complexes is, therefore, an important tool to compare such systems. Here, we evaluate different approaches previously used by the community, showing a global nonlinear fit procedure to yield the most reliable results.